2021
DOI: 10.2174/1570159x18666201008113052
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Role of Neuroserpin in Ischemic and Hemorrhagic Stroke

Abstract: : Tissue plasminogen activator (tPA) is commonly used to treat acute ischemic stroke within an appropriate therapeutic window. Its inhibitor, neuroserpin (NSP), is reported to exhibit neuroprotective effects on stroke. This review aims to summarize, from literature, the available evidence, potential mechanisms, and knowledge limitations regarding the neuroprotective role of NSP in stroke. All the available evidence indicates that regulation of the inflammatory response may play a key role in the mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As the NMDA-R is involved in many diseases and toxicological AOPs (Chen et al 2020 ; Liu et al 2019 ; Sachana et al 2019 ; Tschudi-Monnet and FitzGerald 2019 ; Wang and Reddy 2017 ), agents interfering with its function are a major health concern and need to be identified. An in vitro test method for this purpose would ideally employ human cells and measure a physiological change directly linked to ionotropic glutamate receptors.…”
Section: Introductionmentioning
confidence: 99%
“…As the NMDA-R is involved in many diseases and toxicological AOPs (Chen et al 2020 ; Liu et al 2019 ; Sachana et al 2019 ; Tschudi-Monnet and FitzGerald 2019 ; Wang and Reddy 2017 ), agents interfering with its function are a major health concern and need to be identified. An in vitro test method for this purpose would ideally employ human cells and measure a physiological change directly linked to ionotropic glutamate receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying its neuroprotective role is still debated, including both tPA‐dependent and tPA‐independent pathways 58 . It helps maintain the structure of BBB, protect neurons/astrocytes, and suppress neuroinflammatory responses such as microglial activation after stroke 59 . A recent study reported that intranasal delivery of serpina3n, the mouse homolog of human α1‐ACT, reduced infarct size and rescued neurological deficits after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…These agents include anti-inflammatory factors, antioxidants, glutamate antagonists, neurotrophic factors, γ-aminobutyric acid receptor agonists, calcium antagonists, and free radical scavengers. 27 , 28 These neuroprotective medicines have shown promise in improving the prognosis of ischemic stroke in several preclinical and clinical trials; nevertheless, these results must be further validated and standardized. This necessity arises due to various factors, such as the heterogeneity of stroke in human subjects, the evaluation metrics employed in animal studies, the optimal time window for drug administration, and the influence of brain aging on treatment outcomes.…”
Section: The Ischemic Stroke and Its Treatment Modalitiesmentioning
confidence: 99%